Enhanced Charge‐Carrier Injection and Collection Via Lamination of Doped Polymer Layers p‐Doped with a Solution‐Processible Molybdenum Complex. (17th December 2013) - Dai, An; Zhou, Yinhua; Shu, Andrew L.; Mohapatra, Swagat K.; Wang, He; Fuentes‐Hernandez, Canek; Zhang, Yadong; Barlow, Stephen; Loo, Yueh‐Lin; Marder, Seth R.; Kippelen, Bernard; Kahn, Antoine
<x xml:space="preserve">Abstract</x> Poly(3‐hexylthiophene) (P3HT) is p‐doped by the new soluble dopant molybdenum tris[1‐(methoxycarbonyl)‐2‐(trifluoromethyl)‐ethane‐1, 2‐dithiolene] and investigated via photoemission spectroscopy and transport measurements. Soft‐contact transfer lamination of thin layers of the doped P3HT on undoped polymer layers is used to create spatially‐confined doped regions, which serve as hole‐injection contacts on P3HT diodes. This strategy is then used to create efficient hole‐collecting contacts on solution‐processed inverted polymer solar cells.